Solving the voltage regulation problem with output feedback - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, a power system model is proposed to achieve a decentralized voltage control scheme. A stabilizing controller design is presented to solve the voltage regulation problem with output feedback. The model is intended to be an exact representation of frequency and terminal voltage, which will allow us to cope with time-varying parameter uncertainties, and also unknown design parameters of a power system stabilizer. A quadratically stabilizing output feedback controller is obtained. The design parameters of the power system stabilizer in which the uncertain parameters guarantee quadratic stability are determined. A bisection algorithm procedure is introduced to find the maximum value of the unknown parameters of the power system stabilizer for which the solution is feasible between allowable intervals of uncertain parameters in the model. © 2017 IEEE.
Keywords: Bisection algorithm; Output feedback control; Voltage regulation